Histological and Micrometrical Studies on the Adrenal Gland of Adult Bakerwali Goat - Kour, Gagandeep; Suri, Shalini; Sarma, Kamal (Indian Journal of Veterinary Anatomy, 2018)
The histological studies were conducted on 50 adrenal gland of adult Bakerwali goats. The adrenal gland shows two main areas; the medulla and the cortex in cross section covered by capsule. The adrenal capsule was significantly thicker in left adrenal gland (1.33.94 ± 2.24μm) than in right adrenal gland (115.17 ± 4.33μm). From the capsule various connective tissue trabeculae descend into the stroma and varied widely in thickness (9.52 -19.04μm). In Bakerwali goat, the adrenal cortex consisted of three zones i.e. zona glomerulosa, zona fasciculata and zona reticularis. The total cortical thickness was recorded significantly more in left adrenal gland (2769.58 ± 49.70μm) than in right adrenal gland (2502.35 ± 42.18μm). The total thickness of adrenal medulla was greater in left adrenal gland (2892.14 ± 49.78μm) than in right adrenal gland (2784.76 ± 14.68μm) in Bakerwali goat but statistically non significant. The central vein was located in the centre of the adrenal gland and was lined by endothelial cells. The diameter of the central vein was more in left adrenal gland (78.33 ± 1.00μm) than right adrenal gland (58.78 ± 2.84μm) of adult Bakerwali goat.